Development of Entrepreneurship Management e-Module Using Brainstorming-Based Professional Flip Pdf to Build Student Entrepreneurial Characteristics - Wardani Purnamasari; Wati Wati; Meri Rahmania (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
This research is motivated by the lack of development of innovative teaching materials in the learning process, referring to the era of industrial globalization 4.0 which demands the availability of learning resources by utilizing technological sophistication to facilitate users in the learning process. In this research, we develop an E-module with the help of the Flip PDF Professional application in entrepreneurship learning. Where in this study an entrepreneurial management module was developed which was designed in accordance with brainstoarming with the aim of growing the entrepreneurial characteristics of students. This study aims to produce an entrepreneurship management e-module with the help of a valid and practical Flip PDF Professional application based on the brainstorming method in order to cultivate the entrepreneurial characteristics of students. The type of research used is development research with ADDIE design. The data were collected by using a questionnaire technique using a module validation questionnaire sheet instrument and a practicality questionnaire. Data were analyzed using quantitative descriptive in the form of average percentage. The results showed that: (1) the developed e-module was at a very valid validity level with a validity value of 85%, (2) the e-module developed was at a very practical practicality level, with a practicality value of 81.79%.